Refugee Children's Participation in the Women, Infants, and Children Supplemental Nutrition (WIC) Program in Massachusetts, 1998-2010. Issue 1 (January 2019) - Smock, Laura; Nguyen, Thinh; Metallinos-Katsaras, Elizabeth; Magge, Hema; Cochran, Jennifer; Geltman, Paul L.
Abstract : Objectives: To (1) describe prevalence of growth abnormalities and anemia in refugee children; (2) describe the proportion of age-eligible refugee children enrolled in Special Supplemental Nutrition Program for Women, Infants, and Children (WIC); and (3) identify risk factors for lack of enrollment in WIC. Design: Data were collected from 1731 health screenings for refugee children younger than 5 years in Massachusetts in 1998-2010 and matched to WIC program records. Risk factors for lack of WIC enrollment were analyzed in SAS using multivariate logistic regression. Setting: Massachusetts. Participants: Refugee children under age 5 years. Main Outcome Measures: (1) prevalence of growth abnormalities and anemia in refugee children, (2) proportion of age-eligible refugee children enrolled in WIC, and (3) association of risk factors with lack of WIC enrollment. Results: Overall, 33% of refugee children under age 5 in Massachusetts had at least 1 growth and nutrition problem, including anemia (31%), stunting (10%), wasting (8%), and low weight for age (10%). WIC enrollment among refugee children under 5 years of age was only 62%, lower than that of all eligible children under 5 in Massachusetts (86%). Risk factors for lack of WIC enrollment among refugee children included age, world region of origin, and arrival cohort. Conclusions: Although many refugee children under age 5 experience growth or nutrition problems, one-third of refugee children in Massachusetts were not enrolled in WIC for nutrition assistance, representing a failure of the system. Agencies providing services at the local level should be supported to facilitate enrollment and participation for shared clients.